Improving power smoothing and performance of pitch angle system for above rated speed range in wind power systems. Issue 3 (11th January 2019) - Gholami, Mehrdad; Fathi, Seyed Hamid; Milimonfared, Jafar; Chen, Zhe
Abstract : This study presents a new simple control strategy for direct driven permanent magnet synchronous generator wind turbines, using no wind speed sensor. It is shown that the fluctuation in output power, not only exists at below the rated wind speed, but also appears in above the rated speed region. Therefore, it employs power‐smoothing strategies within a wide range of wind speeds and provides soft performance of the pitch angle system for above the rated speed range. In previous studies, power smoothing is mainly limited to the wind speeds below the rated value, whereas, in this study, all operating speed ranges of the turbine, including wind speeds above the rated value, are considered. Fluctuation in the output power for above the rated speed is analysed and it is shown that there is a significant level of fluctuation in the output power. Therefore, a new strategy is proposed to have more power smoothing as well as having soft performance of pitch angle system for above the rated speed region. The performance of the proposed strategy is evaluated by MATLAB/ Simulink simulation and its validity and effectiveness are verified.